Coagulation abnormality as a complication of L-asparaginase therapy in childhood lymphoblastic leukemia - Djajadiman Gatot; Keumala Pringgardini; Rulina Suradi (Paediatrica Indonesiana, 2006)
Background Bleeding, one of the most common symptoms ofacute leukemia in untreated patients, is mostly due to thrombocy-topenia as a result of myeloinvasion by leukemic cells. Neverthe-less, a further contributory factor for the additional hemorrhagiccomplication during intensive chemotherapy is the myelosuppressiveeffect of most active drugs. L-asparaginase, one of the cytostaticsused during remission induction therapy for childhood of acutelymphoblastic leukemia (ALL), is widely reported to impair the he-mostatic system.Objective To determine the influence of shorter courses of L-as-paraginase (L-Ase) on some of the hemostatic parameters in thetreatment of childhood ALL.Methods A prospective analytical study was carried out in theDepartment of Child Health, Cipto Mangunkusumo Hospital Jakartafrom July 1, 1999 to June 30, 2001 on newly diagnosed ALL pa-tients with normal liver function tests treated according to our na-tional ALL protocol which one of its composition contained 6 in-stead of 9 injections of L-asparaginase.Results All of 30 children with ALL included in the study, experi-enced prolongation of prothrombin time (PT), activated partialthromboplastin time (aPTT), and decreased fibrinogen concentra-tion, markedly during the administration of L-asparaginase. How-ever, none of the patients had additional hemorrhage or evidenceof disseminated intravascular coagulation (DIC).Conclusion The use of shorter courses of L-asparaginase, 6 in-jections, in the remission induction chemotherapy of childhood ALLin our department may reduce the blood clotting factors withoutfurther hemorrhage complication or evidence of DIC